Seismic Hazard Assessment in Gorontalo: Subduction Zone and Earthquake Analysis - Icha Untari Meidji; Dewa Gede Eka Setiawan; Irsan; Kartika; Harsano Jayadi (Postgraduate, University of Mataram, 2025)
The Gorontalo region is one of the regions on the island of Sulawesi that is quite significant in terms of tectonic activity due to earthquakes. This is because Gorontalo is located in a tectonic environment, with a subduction zone in the Sulawesi Trench north and the Balantak Thrust and Batui Thrust south of the Gorontalo Fault. To further understand Gorontalo's seismic activity, we conducted a seismotectonic analysis in the form of identifying the number of earthquakes from 1994 to 2025, interpreting the results of the focal mechanism distribution by classifying them in the Kaverina diagram, and analyzing the results of earthquake hypocentre relocation from 2015 to 2022. The study results show that 2.317 earthquake events over 30 years spread across all areas of Gorontalo, categorised as shallow, medium, and deep earthquakes. The Gorontalo area is dominated by reverse faulting focus mechanisms, which are commonly found at shallow to intermediate depths. This is interpreted as being due to the presence of a subduction zone. A different situation occurs at deep depths, where the focal mechanism is normal faulting, indicating the presence of extensional forces due to the rollback slab process. The distribution of earthquake mechanisms also shows that a combination of strike-slip and reverse mechanisms occurs around active fault zones. In contrast, strike-slip mechanisms with standard mechanisms are more dominant in extensional zones.